Functional outcome of surgical management of distal humeral fracture with precontoured anatomical locking plate - Japatti, Manjunath S.; Janardhan, Pavith T. (International Journal of Research in Medical Sciences, 2021)
Background: Intra-articular distal humeral fractures are among the common fractures seen in adults. The cause of injury most commonly being road traffic accidents. These fractures require fixation methods which are technically difficult to achieve a good functional outcome and to minimize complications. This study was useful to analyse the above factors, to come to conclusion. Methods: This was a prospective study of 20 cases of supracondylar fracture humerus with intercondylar extension treated surgically and assessed for functional outcome, which were admitted to our hospital between 2015 to 2017. Precontoured distal humerus anatomical locking plates were used for fracture fixation with various standard approaches to elbow. Various clinical and functional outcome were analysed at the end using mayo elbow performance score. Results: Out of 23 patients, 20 patients were available for final follow up and outcome analysis. There were 15 males and 5 females with an average age of 34.4 year (21-50 years). Average time between admission and surgery was 4 days. Clinical and radiological consolidation of fracture was observed in all cases at an average of 12 weeks (9-14 week). The results obtained using mayo elbow performance score were graded as excellent 10 (50%) patients, fair in 6 (30%), poor in 4 (20%). One case had superficial wound infection and managed with IV and oral antibiotics. One patient had transient ulnar nerve palsy managed conservatively and recovered. Conclusions: Open reduction and internal fixation with anatomical precontoured locking plate is the treatment of choice in comminuted intercondylar distal humerus fractures. specially in young active adults. It provides stable fixation and thereby facilitating early postoperative rehabilitation. However, the outcome mainly depends on restoring the anatomic nature of articular surface along with minimal soft tissue destruction.